Production components in transformed and untransformed ‘Micro-Tom’ tomato plants (Revista Ciência Agronômica, 2023)
Changes to the amounts of certain proteins have resulted in several studies, among them the so-called heat shockproteins (HSP), which take many forms, most of them constitutive. However, other forms may be inducible by a particularstress factor. The ‘Micro-Tom’ tomato is considered a model for experimental studies due to having suitable characteristics,such as reduced size, short generation time, and ease of transformation. Growth and production components were thereforeevaluated in ‘Micro-Tom’ tomato plants transformed for different levels of mitochondrial HSP (MT-sHSP23.6). Plants fromgenotypes of the ‘Micro-Tom’ tomato (untransformed, and transformed with overexpression and with expression silencing)were grown under controlled conditions of temperature, photoperiod and photon flux density. To obtain the data, successivecollections were carried out at regular intervals (21 days) throughout the development cycle of the plants, starting from the 21stday after transplanting (DAT). Total dry matter, leaf area, dry-weight partitioning between the plant organs, and productioncomponents were determined in the three genotypes. From interpretation of the results, it was found that plants transformedwith overexpression of MT-sHSP23.6 displayed greater production capacity, considering the fresh weight of the fruit; but ingeneral, the data showed that genetic transformation did not bring about major changes in growth, since the three genotypesdisplayed similar behaviour.